Dosimetric Impact of AAA and AXB Dose Calculation Algorithm in VMAT Treatment Planning for Rectal Tumors - Karthikeyan Srinivasan; Sureka Chandrasekaran Sekaran; Suresh Thangavelu; M. S. Belliappa (Journal of Medical Physics)
Aim: The study aims to compare the accuracy of Anisotropic Analytical Algorithm (AAA) and acuros XB (AXB) dose calculation algorithms for radiotherapy (RT) planning of rectal tumors. Materials and Methods: Treatment plans from 20 patients with previously treated rectal cancer were retrospectively analyzed. All patients underwent VMAT treatment planning using the AAA algorithm in Eclipse (v15.6) system. These plans were recalculated with AXB in Eclipse (v15.6) while maintaining the original multileaf collimator fluence. Dosimetric parameters and gamma analysis (3%/3 mm and 2%/2 mm criteria) were compared between the two algorithms. A paired two-tailed t-test was used to statistically compare dosimetric and gamma analysis results between the AAA and AXB algorithms. Results: The results indicate that AAA could be potentially overestimating the dose to planning target volume (PTV). While the mean bowel dose was marginally lower in AAA plans (P = 0.013), doses to other organs at risk (OARs) were slightly higher, suggesting a general overestimation trend. This implies that AAA could be potentially overestimating the dose to OARs and PTV as compared to AXB. The statistical analysis of the Gamma parameters also shows a significant change. Conclusion: The results indicate that the dose calculation accuracy of AXB is superior to AAA for rectal cancer RT.